Snow White and the seven dwarfs [videorecording (DVD)] - Hand, David, 1900-1986 (Disney DVD : Distributed by Buena Vista Home Entertainment, 2001)
Fairy tale story of Snow White and the adventures she has with the seven dwarfs, the prince, and the evil queen.